1955
DOI: 10.1002/hlca.19550380641
|View full text |Cite
|
Sign up to set email alerts
|

Über die katalytische Reduktion aliphatischer Carbonsäureamide

Abstract: Es wurde die katalytische Reduktion von aliphatischen Carbonsäureamiden zu den entsprechenden Aminen bei Verwendung von Kupfer‐Chrom‐Oxyd als Katalysator untersucht und dabei speziell der Einfluss von organischen Lösungsmitteln und von Ammoniak auf den Reaktionsverlauf geprüft.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…[6] Thea chievement of hydrogenation of amides under mild reaction conditions, ideally lower than 30 bar H 2 and 70 8 8C, [6] is listed as aleading candidate in 12 key innovative research areas for the future sustainable production of pharmaceuticals. [7] In early studies of the hydrogenation of amides,Co, [8] Ni, [9] Cu-Cr oxide, [10] and Re [11] catalysts were found to be effective, but required harsh reaction conditions,n amely 200-370 bar H 2 and 200-300 8 8C. In 1988, Dobson reported ac atalyst with much improved efficiency, namely abimetallic Pd/Re catalyst enabled amide hydrogenation at 130 bar H 2 and 200 8 8C.…”
mentioning
confidence: 99%
“…[6] Thea chievement of hydrogenation of amides under mild reaction conditions, ideally lower than 30 bar H 2 and 70 8 8C, [6] is listed as aleading candidate in 12 key innovative research areas for the future sustainable production of pharmaceuticals. [7] In early studies of the hydrogenation of amides,Co, [8] Ni, [9] Cu-Cr oxide, [10] and Re [11] catalysts were found to be effective, but required harsh reaction conditions,n amely 200-370 bar H 2 and 200-300 8 8C. In 1988, Dobson reported ac atalyst with much improved efficiency, namely abimetallic Pd/Re catalyst enabled amide hydrogenation at 130 bar H 2 and 200 8 8C.…”
mentioning
confidence: 99%
“…[4] Early efforts towards catalytic hydrogenation of amides with heterogeneous catalysts based on copper chromite, [5] rhenium, [6] and Raney catalysts [7] showed that the reaction is, in principle, feasible. [4] Early efforts towards catalytic hydrogenation of amides with heterogeneous catalysts based on copper chromite, [5] rhenium, [6] and Raney catalysts [7] showed that the reaction is, in principle, feasible.…”
mentioning
confidence: 99%
“…Unfortunately, the catalytic reduction of carboxylic acids and their derivatives is highly challenging, with amides being the least reactive motifs. [4] Early efforts towards catalytic hydrogenation of amides with heterogeneous catalysts based on copper chromite, [5] rhenium, [6] and Raney catalysts [7] showed that the reaction is, in principle, feasible. However, harsh reaction conditions, with temperatures of 175-260 8C and high pressures of 100-990 bar, were required in all cases.…”
mentioning
confidence: 99%
“…Unfortunately, the catalytic reduction of carboxylic acids and their derivatives is highly challenging, with amides being the least reactive motifs 4. Early efforts towards catalytic hydrogenation of amides with heterogeneous catalysts based on copper chromite,5 rhenium,6 and Raney catalysts7 showed that the reaction is, in principle, feasible. However, harsh reaction conditions, with temperatures of 175–260 °C and high pressures of 100–990 bar, were required in all cases.…”
Section: Methodsmentioning
confidence: 99%